EFEKTIVITAS COGNITIF BEHAVIORAL THERAPY DENGAN TEKNIK SELF-CONTROL UNTUK MENINGKATKAN KEDISIPLINAN SISWA [THE EFFECTIVENESS OF COGNITIVE BEHAVIORAL THERAPY WITH SELF-CONTROL TECHNIQUES TO IMPROVE STUDENT'S DISCIPLINE] - Nur Wahyudi; C Casmini (Acta Islamica Counsenesia: Counselling Research and Applications, 2021)
Discipline behavior is a manifestation of the individual's ability to control himself. The quality of a person's self-control determines the quality of his discipline, so that each individual must have self-control in improving discipline. Therefore, this study aims to see the effectiveness of cognitive behavior therapy with self-control techniques to improve student discipline. This research is an experimental study with a sample of 8 students. Data collection techniques using a discipline scale, interviews, observations, and documentation. The data analysis technique used paired samples test (T-Test). The results of data analysis t-count is 8.027 and t-table is 2.365, (8.027 2.365). The value of sig (2-tailed) is 0.000 so 0.000 0.05. The results of the study show that cognitive behavioral therapy with self-control techniques is effective in improving student discipline.